2014
DOI: 10.4314/ahs.v13i4.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of moderate versus mild aerobic exercise training on inflammatory cytokines in obese type 2 diabetic patients: a randomized clinical trial

Abstract: Background: Recently some plasma biomarkers of inflammation have been recognized as important cardiovascular risk factors. There is little information about the effects of aerobic exercise training on these biomarkers and the risk of metabolic complications in obese type 2 diabetes patients. Objective: To compare the impact of moderate versus mild aerobic exercise training on the inflammatory cytokines in obese type 2 diabetic patients. Methods: Fifty obese type 2 diabetic patients of both sexes with body mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 36 publications
(40 reference statements)
1
20
0
8
Order By: Relevance
“…However, there is some evidence that aerobic exercise training is anti-inflammatory, and moderate-intensity aerobic exercise has been shown to attenuate the circulating markers of inflammation in both healthy and diseased populations (Tartibian et al 2011, Abd El-Kader et al 2013. Recently, a 3-month randomized trial aerobic exercise training showed reduced plasma concentrations of TNF-α, IL-2 and IL-6 among obese type 2 diabetic patients (Abd El-Kader et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is some evidence that aerobic exercise training is anti-inflammatory, and moderate-intensity aerobic exercise has been shown to attenuate the circulating markers of inflammation in both healthy and diseased populations (Tartibian et al 2011, Abd El-Kader et al 2013. Recently, a 3-month randomized trial aerobic exercise training showed reduced plasma concentrations of TNF-α, IL-2 and IL-6 among obese type 2 diabetic patients (Abd El-Kader et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some evidence that aerobic exercise training is anti-inflammatory, and moderate-intensity aerobic exercise has been shown to attenuate the circulating markers of inflammation in both healthy and diseased populations (Tartibian et al 2011, Abd El-Kader et al 2013. Recently, a 3-month randomized trial aerobic exercise training showed reduced plasma concentrations of TNF-α, IL-2 and IL-6 among obese type 2 diabetic patients (Abd El-Kader et al 2013). Likewise, previous studies have also shown decreases in serum C-reactive protein (CRP), prostaglandin (PG) E 2 , TNF-α, IL-6 and IL-8 levels with 16 and 24 weeks of moderate-intensity aerobic exercise training in postmenopausal women (Tartibian et al 2011(Tartibian et al , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Em todos os estudos o processo de randomização foi descrito e em 10 ECR a sequência de alocação foi descrita [25][26][27][28][29][30]33,35,37,42]. O processo de cegamento dos participantes, cuidadores e avaliadores foi descrito em oito estudos [11,18,26,27,32,38,41,43]. Nenhum dos estudos apresentou a descrição dos processos de cegamento dos resultados.…”
Section: /11unclassified
“…O cálculo do tamanho amostral não foi apresentado consistentemente nos artigos, tornando difícil a interpretação dos achados devido ao poder insuficiente em seis estudos [32,40,[43][44][45][46]. A intervenção foi baseada em exercícios aeróbios em sete estudos [25,28,30,33,36,37,43] com duração entre 30 e 75 minutos por sessão com intensidades entre 50 e 85% do VO 2 máximo e entre 65 e 75% da frequência cardíaca máxima (FCM).…”
Section: /11unclassified
“…12 Exercise training reduces pro-inflammatory biomarkers, 13 with several studies reporting that moderate intensity exercise decreases inflammation compared to low intensity exercise. 14,15 However, the effects of higher intensity aerobic exercise on inflammatory biomarkers in patients with…”
Section: Introductionmentioning
confidence: 99%